Pengaruh Kepemilikan Institusional, Komisaris Independent, Komite Audit, Intensitas Modal, dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak - Fatimah Kusumawardani; Ashari Ashari; Alfiyani Nur Hidayanti (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2023)
This study was conducted to examine the effect of institutional ownership, independent commissioners, audit committees, capital intensity, and sales growth on tax avoidance. The population in this study are companies in the consumer cyclicals and consumer non-cyclicals sectors that are listed on the Indonesia Stock Exchange for the 2017-2021 period. The data in this study uses secondary data. The sampling technique used purposive sampling method, so as to obtain a sample of 190 companies. The analysis technique used is multiple linear regression analysis using SPSS statistics version 25 application. Based on the analysis results of this study indicate that institutional ownership, audit committees, and capital intensity have no effect on tax avoidance. Meanwhile, independent commissioners and sales growth have a negative effect on tax avoidance.